Mass Spectrometric Analysis of Multiple Pertussis Toxins and Toxoids. (23rd May 2010) - Williamson, Yulanda M.; Moura, Hercules; Schieltz, David; Rees, Jon; Woolfitt, Adrian R.; Pirkle, James L.; Sampson, Jacquelyn S.; Tondella, Maria L.; Ades, Edwin; Carlone, George; Barr, John R.
Abstract : Bordetella pertussis (Bp) is the causative agent of pertussis, a vaccine preventable disease occurring primarily in children. In recent years, there has been increased reporting of pertussis. Current pertussis vaccines are acellular and consist of Bp proteins including the major virulence factor pertussis toxin (Ptx), a 5-subunit exotoxin. Variation in Ptx subunit amino acid (AA) sequence could possibly affect the immune response. A blind comparative mass spectrometric (MS) analysis of commercially available Ptx as well as the chemically modified toxoid (Ptxd) from licensed vaccines was performed to assess peptide sequence and AA coverage variability as well as relative amounts of Ptx subunits. Qualitatively, there are similarities among the various sources based on AA percent coverages and MS/MS fragmentation profiles. Additionally, based on a label-free mass spectrometry-based quantification method there is differential relative abundance of the subunits among the sources.